Safe Handling of Cytotoxic Drugs and Risks of Occupational Exposure to Nursing Staffs - Somayeh Hanafi; Hassan Torkamandi; Sahar Bagheri; Maria Tavakoli; Naser Hadav; Mohammadreza Javadi (Research Center for Rational Use of Drugs (RCRUD), 2016)
Background: Inherent toxicity of cytotoxic drugs is the basis for their potential adverse risks from occupational exposure to the nursing staff. In Iran, chemotherapy regimens are prescribed and administered according to the world updated protocols. But little is done regarding the protective standards in this field. Methods: An observational cross-sectional survey was conducted among nurses who work in three tertiary care teaching hospitals in Tehran, Iran in 2012. All participants worked in one of the hospital wards handling cytotoxic drugs (preparation and administration). A questionnaire was used for interviewing all subjects, and observing them preparing and administering the drugs. We examined all adverse effects associated with handling of antineoplastic drugs. Results: Totally 270 adverse reactions were reported. The most frequently reported adverse effects included headache and vertigo (40 cases), hair loss (36 cases), skin rashes and itching (31 cases), and burning sensation in eyes (31 cases). In all hospital wards, the standards were met in not more than 50% of the items. Conclusion: Monitoring the personnel who are directly involved in handling of cytotoxic drugs is of great importance. Furthermore, educating the personnel in the field of standards of cytotoxic drugs handling could increase the nursing staff's knowledge regarding these drugs' adverse reactions.